Financial Ratio Analysis To Assess Financial Performance At Pt. Perkebunan Nusantara Iv Medan 2018-2022. - Damanik, Dicky; Junaidi, Koko (Agriprimatech, 2025)
The researchlconducted by the author aimsltoldetermine: (1) thelfinancial performanceloflPT. Nusantara IV Plantation Medanlis basedlon the LiquiditylRatio inlterms oflthe Cash Ratioland currentlratio. (2) financiallperformance oflPT. Perkebunan Nusantara IV Medan basedlon profitabilitylratios inlterms oflReturn OnlInvestment andlReturn OnlEquity. (3) financiallperformance oflPT. PlantationlArchipelago IVlMedan basedlon thelsolvencylratio inlterms oflthe DebtlRatio. (4) financiallperformance oflPT. Perkebuanan Nusantara IV Medan is based on the activity ratio in terms of total asset turnover. Thislresearch waslconducted atlPT. Nusantara IV PlantationlMedan. Thelapproach usedlis aldescriptivelapproach. Theldata analysisltechniques usedlin thislresearch is descriptivelanalysis techniques and time series analysis techniques, namelylcollectldata, clarifyingldata, explanationldata andlanalyzingldata. Theldata usedlis thelPT balance sheet. Perkebunan Nusantara IV Medan forlthe periodl2018-2022. Theldata collectionltechnique used isldocumentationlstudy, namelylstudy documentslrelated tola data research problemlsuch aslcompany financeldata reportslobtained directlylfrom thelcompany. Thelresults achieved from thislresearch providelthe conclusionlthat financial performance is based on Cash Ratio, CurrentlRatio, Returnlon Investment, ReturnlonlEquity, DebtlRatio, andltotal assetslturnover.